Water quality in major land use systems of Western ghats in Kottayam and Idukki districts of Kerala - Prasannakumari P; Jacob J; Jessy M.D; Pradeep B; Ulaganathan A (PLACROSYM XXIII. Climate Resilient Technologies for Sustainability of Plantation Crops, 6-8 March 2019, Central Coffee Research Institute, Chikkamangaluru, Karnataka, India, Abstracts, p.65.)
A study was conducted during the period 2015-17 to assess the water quality in rubber, tea and cardamom dominated watersheds in the Western Ghats of Kottayam and Idukki districts in Kerala state. Watersheds (of about 18-30 km2 area) were delineated using survey of India topographic maps, satellite images and field information. Watershed dominated by rubber plantations (30.3 km2 area) was delineated at Poonjar area which is on the western slope of the Western Ghats, in Kottayam district. Watersheds of tea (20.5 km2 area) and cardamom plantations (18.6 km2 area) were delineated at Vandipperiyar and Udumbanchola areas respectively in Idukki district. Sampling sites were identified depending on watershed and accessibility after detailed field investigations to ensure distribution. Water samples were collected during post-monsoon season of 2015, pre- and post-monsoon seasons of 2016 and pre-monsoon season of 2017, and analyzed for important physico-chemical parameters following standard protocols. Bacteriological analysis was carried out during the first two sampling seasons. Pesticide residue analysis of selected samples was carried out during pre-monsoon season 2017. The study showed that total dissolved solids, total hardness and electrical conductivity were significantly higher in groundwater and surface water in watersheds of tea and cardamom compared to that in rubber watershed. Significantly higher contents of calcium, magnesium, potassium, sodium and nitrate were also observed in samples from watersheds of tea and cardamom compared to rubber. The results indicate higher run off and leaching of nutrients from tea and cardamom plantations consequent to the higher agricultural inputs in the cultivation of these crops. Though the effect of agro-management practices was reflected in the physico-chemical properties of ground water and surface water, all these parameters, except pH of ground water in tea watershed, were within the limits specified for drinking water. Heavy metal contents also were within acceptable limits in the three watersheds. Bacteriological analysis confirmed the presence of fecal coliform bacteria in groundwater and surface water samples of all three watersheds. Analysis of water samples for pesticide residues showed that organo-chlorines, organo-phosphates and pyrithroides were below detection limit in all three watersheds. Bacterial contamination is the major water quality problem in these plantation areas rendering the water unsuitable for drinking purpose. Dissolved oxygen content of surface water was significantly higher in samples from rubber watershed compared to tea and cardamom, indicating better health of water resources in rubber system. DO values lower than the WHO specified limit of 6.0 mg/l limit were observed in tea watershed during all the four measurements. Low dissolved oxygen levels in surface water and acidic pH of groundwater in tea watershed indicate deterioration of water quality in tea system. Bacterial contamination is the major water quality problem in these plantation areas rendering the water unsuitable for drinking purpose.
Keywords: Cardamom; Land use; Rubber; Tea; Water quality